Rancang Bangun Sistem Informasi Akademik Menggunakan Framework Codeigniter Pada universitas Muhammadiyah Purworejo - Widatama Krisna; Hamid Jumasa Muhammad; Nadia Ambadar (Jurnal Sistem Cerdas, 2022)
Academic Information System is a system that provides services that are academic data information designed in accordance with business processes that run to improve the performance and quality of academic services. This academic information system has many benefits for institutions in the field of education, be it in the processing of teaching data, value data, and other data related to academic learning in this case, especially universities. The problem that exists today is the absence of an academic information system at the University of Muhammadiyah that is able to store all academic data. Therefore, academic information systems that can meet the needs are very necessary. This research discusses the design of web-based systems using codeigniter 3 framework which is expected to produce an academic information system that meets the needs.